(untitled) (The Pakistan Development Review, 2019)
Fareeha Zafar’s book Canals, Colonies and Class: British Policy in the Punjab 1880-1940 is essentially an edited reproduction of her PhD thesis, The Impact of Canal Construction on the Rural Structures of the Punjab: The Canal Colony Districts, 1880 To 1940. The thesis was completed about 35 years ago at the School of Oriental and African Studies, the University of London (now SOAS, the University of London). She studies the British colonisation process in the Punjab and its effect on the local environment, the production patterns, and social relations, understanding that despite several similar studies on the region, no serious effort had been made to synthesise these issues the way she does in this book. However, in the form of a new book, the synthesis does not add much value as it reiterates the British colonisers’ well-known strategies, namely irrigation development as a tool to settle disarmed forces and nomads and, thereby, strengthening a class of local landed elite to maintain their power in the colonies, their revenue-seeking policies, indebtedness of the landed class and alike. Nevertheless, considering the timing of the original contribution, the book, if read together with the contributions such as Khuhro (1978/1999) and Cheesman (1997), provides a relatively rich description of geographers’ analyses of the British policies, their intentions, and their effects.